2001
DOI: 10.1002/pros.1056
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in organ‐confined prostate cancer by gene expression array

Abstract: GST-based metabolism, cytokine MCP-1 and TNFR-1, and TGF-beta3 signaling pathways, and some helix-loop-helix nuclear proteins could be potentially important in organ-confined prostate cancer and deserve further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 18 publications
6
58
0
Order By: Relevance
“…Annexin II does not affect prostate cancer cell-cycle progression or apoptosis Although our observations so far (Figures 1-4; Table 1) and others' (Paweletz et al, 2000;Chetcuti et al, 2001) suggest that reduced or lost expression of annexin II (or annexin I) may contribute to prostate cancer development/progression, this possibility has not been directly tested. Since annexin II is reduced in prostate cancer cells, the molecule may normally suppress prostate cancer development by restricting cell proliferation, promoting programmed cell death (apoptosis), or by limiting cell migration and invasion.…”
Section: Reduced As Well As Altered Expression Patterns Of Annexin IImentioning
confidence: 56%
See 2 more Smart Citations
“…Annexin II does not affect prostate cancer cell-cycle progression or apoptosis Although our observations so far (Figures 1-4; Table 1) and others' (Paweletz et al, 2000;Chetcuti et al, 2001) suggest that reduced or lost expression of annexin II (or annexin I) may contribute to prostate cancer development/progression, this possibility has not been directly tested. Since annexin II is reduced in prostate cancer cells, the molecule may normally suppress prostate cancer development by restricting cell proliferation, promoting programmed cell death (apoptosis), or by limiting cell migration and invasion.…”
Section: Reduced As Well As Altered Expression Patterns Of Annexin IImentioning
confidence: 56%
“…The annexin II in protein spot 2 (Figure 1b, d) was not detected by the polyclonal anti-Bim antibody on Western blot (Figure 1b, b), either because the protein level was too low, or more likely because this protein spot represented a post-translationally modified annexin II (thus a different pI), which was not recognized by the antibody. Recently, two groups (Paweletz et al, 2000;Chetcuti et al, 2001) reported reduced/lost expressions of annexins I and II in human prostate cancer tissues. Interestingly, annexin I has been reported to be upregulated in human mammary adenocarcinoma cells (Ahn et al, 1997;Pencil and Toth, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we describe a novel in silico approach to identify potential targets of methylation in prostate cancer. We employed transcriptomic databases and microarray experiments that provided detailed data summaries and focused on expression changes in early-stage disease (Chetcuti et al, 2001;Ashida et al, 2004) and in the progression to metastatic disease (Bubendorf et al, 1999;Dhanasekaran et al, 2001). Interestingly, a common finding between these studies was that downregulation rather than upregulation, accounted for the majority of differentially expressed genes in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Digital Differential Display (http:// www.ncbi.nlm.nih.gov/UniGene/ddd) was used to report on significant differences in gene expression between four different tissue pools, created from libraries of ESTs from normal prostate, primary and metastatic prostate cancer and PIN (Wheeler et al, 2001). The data from four independent, published microarray studies that quantified gene expression at different stages of prostate cancer were also examined (Bubendorf et al, 1999;Chetcuti et al, 2001;Dhanasekaran et al, 2001;Ashida et al, 2004).…”
Section: In Silico Mining To Identify Novel Targets Of Methylation Inmentioning
confidence: 99%